MOTOR AND EDUCATION BENEFITS FOR CHILDREN, THE FUTURE OF MANKIND (Fiep Bulletin - online, 2014)
Physical activity taught to children in particular. It is statistically proven that the child, through physical activity, learn the gesture seeing (83%), listening to what is said by the instructor (13%) and run (1%),The formation of the motor system goes through the following stages: 1. knowledge and observation of the movement; 2. perception and possession of the movement; 3. refinement of movement (mastery). This last phase takes place in phases: - The child learns to perform the act; - The child performs the act economically; - The child performs the gesture in a refined way. A large motor skill is the cause of education and the development of motor skills, which allow the child to gradually transform the basic motor patterns (running, jumping, throwing, receiving, etc.) In specific motor skills (running, change of speed, meaning, direction, hand gliding, dribble, shoot, pass). In fact one cannot speak of technical perfection, until the motor system is not formed. The moment has been reached this milestone, you can refine the movement, in fact, it passes from the structuring and from the knowledge of his own body to the automation of the gesture or movement, taking into account that already from the first phase of training starts the perfecting. The child, in game situation, has to run (thrust force of the lower limbs and speed of execution), change of velocity (direction, sense), but there is a clarification to do it should not be a race typical sprinter, but it must be a race interrupted at the right time to then be run another movement and must be done with great timing, but the baby is often not able to do anything, so it must be educated. The child must be accustomed to control their own bodies, it must be able to be in equilibrium, it must be quick, these skills that need to be educated and developed at the right time. In the gym instructor should provide for all the family of the exercises she jumps, which jumps, hops, jumps in all shapes, play with space, with time, with your body, playing to dribble, shoot, pass and receive , random, all in the form of contests, games, relays and circuits. Children should learn by playing, not through the automation of actions, it is also important as competence and the ability to know your body, space, time, rules, regulations, mates, opponents, through the education and capacity building sense-perception, the motor patterns, skills and motor skills. In children, we must insist and develop coordination skills, joint mobility, ability to structure conditionals, respect the different stages of learning ahead of time and not expect the perfect execution of a single gesture or a movement. As a result, you do not have children build robots, or robots, but people thinking, creative, they can make mistakes, they can progressively improve their ability to play, therefore, stresses the importance of education at an early age in favor of multilateral acquisition of sports techniques correct, but no technique too early.
Keywords: activity motor; motor gesture; enable motor; benefits of exercise